EFEK ANTIOKSIDAN FRAKSI ETIL ASETAT MINUMAN SINOM CAMPURAN JERUK NIPIS DAN MADU (curcuma domestica val-tamarindus indica L.) TERHADAP GULA DARAH TIKUS PUTIH SPRAQUE DAWLEY DIABETES MELITUS - N. K. Wiradnyani; I M. M. Arimathea (Jurnal Kimia (Journal of Chemistry), 2019)
Sinom drinks mixed with lime and honey are made from rhizome of turmeric and young tamarind leaves which are added with lime juice and honey. The aim of the study was to determine the effect of antioxidant compounds of ethyl acetate on sinom drinks mixed with lime juice and honey (SCJM) various doses on fasting blood sugar spraque dawley (SD) white rats diabetes mellitus. Experimental research using RAK, ANOVA analysis with further BNT testing consisted of two stages: 1) test the antioxidant capacity of various solvents of SCJM yielding 29691.1 µg AAEAC / g ingredients namely the highest number of ethyl acetate fractions of n- hexane, chloroform, and water. Phase 2 Ethyl acetate fraction of SCJM was further tested in vivo to SD white rats with diabetes mellitus with various doses, namely: control (-) normal mice, 50, 100, 150, 200 mg/dl BW, control (+) of diabetic rats. The results of the study of the effect of the antioxidant compound SCJM ethyl acetate fraction of various doses significantly affected (p <0.01) in decreasing fasting blood sugar (GDP) white SD diabetes mellitus rats, a dose that can reduce the lowest GDP based on statistical tests is 150 mg/kg BW of rats, 168.4 mg/dl from other doses. Keywords: ethylacetate, blood sugar, antioxidant, sinom